Climb ups for getting back up? Parkour`s potential influence on resilience and stress levels during the COVID-19 pandemic. - Habbel, J. T. (Utrecht University, 2021)
Background: The COVID-19 pandemic results in many adverse effects on peoples´ mental health like stress, for which resilience is a protective factor. Resilience can be built up and increased. This research proposed the previously untested idea that parkour could increase resilience and in turn reduce adverse effects on mental health like stress. Methods: 738 included participants (mean age: 30.6, 51.4% male) filled out an online questionnaire including the Brief Resilience Scale (BRS), the Perceived Stress Scale (PSS) and questions about their main sport. Traceurs` (people practicing parkour) stress- and resilience levels were compared to those of people doing other- or no sport. A correlation between stress- and resilience levels, a MANOVA and a mediation analysis (using PROCESS by Hayes) were conducted. Additionally, an ANOVA tested the relationship between traceurs` training experience in years and their resilience. Results: Participants` resilience- and stress levels were significantly strong negative correlated. Traceurs displayed significantly higher resilience- and significantly lower stress than people doing other- or no sport and resilience levels acted as a mediator. Traceurs of varying training did not significantly differ in resilience levels, which was the only not confirmed hypothesis. Conclusion: For the first time traceurs have been shown to have higher resilience- and lower stress levels. This is expected to reduce adverse effects of the Covid-19 pandemic and could have clinical implications. A causal relationship could not be established due to the research design, and suggestions for further research are given.